ODONTOGENIC OSTEOMYELITIS OF THE JAWS IN CHILDREN - Abdumutalipova M. A. (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Odontogenic osteomyelitis is an inflammatory disease of the jawbone caused by tooth-related infections. It is one of the most common infectious bone diseases in children. The peculiarities of its course are associated with the physiological characteristics of a child’s body and the immaturity of their immune system. Due to the active development of deciduous and permanent teeth in children, the risk of developing osteomyelitis is significantly higher. This article provides a detailed overview of the clinical manifestations, diagnostic approaches, and modern treatment methods for this condition.